2015
DOI: 10.1016/j.tcb.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The biological functions of miRNAs: lessons from in vivo studies

Abstract: Despite their clear importance as a class of regulatory molecules, pinpointing the relevance of individual miRNAs has been challenging. Studies querying miRNA functions by overexpressing or silencing specific miRNAs have yielded data that are often at odds with those collected from loss-of-functions models. In addition, knockout studies suggest that many conserved miRNAs are dispensable for animal development or viability. In this review we discuss these observations in the context of our current knowledge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
414
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(427 citation statements)
references
References 142 publications
(148 reference statements)
10
414
0
3
Order By: Relevance
“…Additionally, given that an individual miR is predicted to bind hundreds of potential target mRNA, the notion that only one or two target mRNA are responsible for the large biological effects of dysregulation of a miR is unlikely (2,37). It has been speculated that modest changes in several members of the same pathway lead to significant biological consequences (2, 38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, given that an individual miR is predicted to bind hundreds of potential target mRNA, the notion that only one or two target mRNA are responsible for the large biological effects of dysregulation of a miR is unlikely (2,37). It has been speculated that modest changes in several members of the same pathway lead to significant biological consequences (2, 38).…”
Section: Discussionmentioning
confidence: 99%
“…The processes necessary for the initiation and progression of lung tumorigenesis require vast changes in gene regulation. microRNA (miR) are noncoding RNA (~22 nt) that can regulate the expression of mRNA, typically by binding 3′-untranslated regions (3′-UTRs), leading to decreased translation and/or degradation of the target mRNA (2). Thus, miR are likely well suited to facilitate the many changes required for cellular transformation.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA regulates gene expression by binding to complementary sequences (Vidigal and Ventura 2015). Numerous studies showed the close relationship between microRNA and neuronal development (Behm and Ohman 2016).…”
Section: Microrna-mediated Conversion Into Dopamine Neurons From Fibrmentioning
confidence: 99%
“…13 These endogenous noncoding RNAs bind to the 3 0 untranslated region (UTR) of their target genes and repress their translation.…”
mentioning
confidence: 99%